Politics and arts: The transformation of the Kurdish oppositional music in Turkey - Arda, Talat Balca. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This study examines the question concerning the formation of the Kurdish political identity through the works of art and the transformation of “the Kurdish Resistance” in Turkey. To develop answers to these questions I investigated several Kurdish oppositional music groups that are popular in Turkey and worldwide. By focusing on the activities of the MKM (Mezopotamya Kültür Merkezi / Mesopotamia Cultural Center) and its members composed of the Kurdish musicians, managers and administrators, I try to show the current dynamics in the formation of the Kurdish resistance through the works of art. At this point, I particularly focus on the transformation of the representation of the Kurdish political movement through music and art by comparing its evolution vis-à-vis the recent liberal approach of the government party the AKP (Adalet ve Kalkınma Partisi / Justice and Development Party) to the Kurdish question that is popularly called as the “Democratic Opening Policy” or shortly “the Democratic Opening” which is firstly declared to public as Kurdish Opening in mid 2009. I concluded that the Kurdish movement together with its cultural institutions do not welcome the Democratic Opening Politicies by claiming that the AKP government misrepresents the Kurdish problem, reduces it to a problem of cultural minority whereas the Kurdish question is a political question that asks for a constitutional transformation to satisfy the demands of the Kurds concerning political autonomy and self government as well as official education in the Kurdish language. In my interviews that I conducted with the artists and other members of the Kurdish cultural institutions they express these critiques through describing the new approach of the AKP to the Kurdish question as an “insincere” move. Throughout the research I tried to analyze how the criteria and definition of being and claiming an oppositional Kurdish artist has changed in time according to the transformation of the political sphere in Turkey and in the world. At this point, I also tried to describe the formation of the Kurdish national imaginary through the art.
Keywords: Art -- Political aspects.; Kurds -- Music.